Analysis of translation of figures of speech into english, spanish and turkish - Natalya Anatolyevna Deputatova, Leysan Ravilevna Vasilova, Zubayda Albertovna Biktagirova,; Habibovich Kasimov, Olimjon (Opción, 2019)
The article is dedicated to the analysis of the translation of figures of speech in the first chapter of the poem by a famous Soviet futurist poet via component and content analysis and comparison. The results of our work show that it is difficult yet possible to translate stylistic figures, even we are talking about a poet having a very unusual style and language. In conclusion, the translators managed to save most of the author’s figures of speech. Nevertheless, none of the neologisms from the original text were saved, and it had an impact on the expressiveness of the poem